Association between MTNR1B polymorphisms and obesity in African American: findings from the Jackson Heart Study - Cynthia Tchio; Solomon K. Musani; Alexander Quarshie; Gianluca Tosini (BMC, 2021)
Abstract Background Melatonin is a hormone that is secreted at night by the pineal gland. It exerts its function by binding to the MT1 and MT2 receptors, which are encoded by the MTNR1A and MTNR1B genes, respectively. Previous studies reveal that MTNR1B variants are associated with insulin secretion impairments and an increased body mass index (BMI) in individuals of European and Asian ancestries. Obesity is highly prevalent in the US and disproportionately affects African Americans. Here, we hypothesized that common single nucleotide polymorphisms (SNPs) imputed in 1000 Genomes in the MTNR1B gene are associated with adiposity in African American adult men and women and that the association is modified by insomnia. Methods We used an additive genetic model to describe the association between the adiposity traits (BMI and waist circumference) and selected MTNR1B variants in 3,029 Jackson Heart Study participants, with an average age of 55.13 ± 12.84 years, and 62% were women. We regressed the adiposity measures on the estimated allelic or genotypic dosage at every selected SNP and adjusted for age, sex, population stratification, and insomnia. Thirty common SNPs, spanning the MTNR1B gene, with a minor allele frequency ≥ 5%, a call rate ≥ 90%, a Hardy-Weinberg equilibrium p value > 10-6, were available for the analysis. Results The allele T of rs76371840 was associated with adiposity (OR = 1.47 [1.13-1.82]; PFDR-adjusted = 0.0499), and the allele A of rs8192552 showed a significant association with waist circumference (β = 0.023 ± 0.007; PFDR-adjusted = 0.0077) after correcting for multiple testing. When insomnia was included in the adiposity analysis model, the following four variants became significantly associated with adiposity: rs6483208; rs4388843; rs4601728; and rs12804291. Conclusions Our data indicate that polymorphisms in the MTNR1B gene are associated with obesity traits in African Americans. To the best of our knowledge, this is the first study to explore the effect of insomnia on the association between the circadian MTNR1B genetic variants and metabolic traits in an African American sample population. We observed that insomnia affected the association between the MTNR1B variants and adiposity.